Numerical simulation of highly efficient lead-free perovskite layers for the application of all-perovskite multi-junction solar cell - Singh, Neelima; Agarwal, Alpana; Agarwal, Mohit (Superlattices and microstructures, 2021)
The numerical simulation of lead-free perovskite cesium tin germanium halide (CsSnGeI3) and methyl ammonium germanium halide (CH3NH3GeI3) solar cells have been performed. It has been elucidated from the numerical simulation that as compare to the CH3NH3GeI3 based structure, CsSnGeI3 based structure depicts better photovoltaic performance under constant illumination condition. To enhance the device photovoltaic performance, the effects of different hole transport layer (HTL), defect density of the absorber layer, metal work function and the effect of temperature has been studied. In the present investigation, the effect of hole transport layers are analyzed by correlating the built-in voltage (Vbi) with the open circuit voltage (VOC). It has been obtained from the simulation results, that Vbi has a significant impact on VOC as the higher Vbi corresponds to the highest VOC. Moreover, the effect of defect density and metal work function is also studied. It is obtained from the simulation results, that the optimum defect density is found to be 1 × 1014 cm−3 and metal work function should be greater than or equal to 5 eV for both lead-free CH3NH3GeI3 and CsSnGeI3 based perovskite layer. Furthermore, to suggest possible lead-free alternatives for all-perovskite two-terminal multi-junction solar cell, an attempt is made to match the current of bottom perovskite layer i.e., CsSnGeI3 based perovskite layer to the top perovskite layer i.e., CH3NH3GeI3 based perovskite layer. To attain the current matching for bottom perovskite layer (CsSnGeI3 based perovskite layer) to top perovskite layer (CH3NH3GeI3 based perovskite layer), the bottom perovskite sub cell is fed with the filtered spectrum which is obtained by transmission from top electrode. After, the realization of current matching the short circuit current density of CsSnGeI3 based perovskite layer drops from 25.75 mA/cm2 to 15.32 mA/cm2 which is similar to CH3NH3GeI3 based perovskite absorber layer. In addition, it has been obtained from literature, that both the perovskite layers can be fabricated using solution–processing low-temperature technology. Hence, the numerical study suggests the possible alternatives for wide and narrow bandgap perovskite layers for the application to obtain highly efficient lead-free all-perovskite multi-junction solar cells. •The numerical simulation of lead-free wide and narrow bandgap CH3NH3GeI3 and CsSnGeI3 perovskite layers is performed.•The effect of different hole transport layers is realized by correlating Vbi with the VOC.•Cu2O as an HTL shows highest Vbi and hence shows better photovoltaic performance.•The study of defect density, metal work function and temperature are explored for lead-free perovskite layers.•The lead-free perovskite layers proves to be the promising candidate for all-perovskite multi-junction solar cell.